Unlocking the Potential of Metaverse Technology: A Novel Approach to Enhancing Digital Skills and Collaboration in Virtual Workspaces - Kustiyono Kustiyono; Asrini Mahdia; Dedi Muliadi; Abeda Muhammad Iqbal (Management Dynamics: International Journal of Management and Digital Sciences, 2024)
The integration of metaverse technology in employee training has the potential to significantly enhance digital skills, collaboration, and overall learning outcomes in virtual workspaces. This study explores the effectiveness of metaverse-based training compared to traditional methods, focusing on participant engagement, learning retention, and practical application in immersive virtual environments. The results indicate that metaverse technology leads to increased participant engagement, offering real-time communication, interactive simulations, and realistic task scenarios that foster deeper involvement and better skill acquisition. Additionally, the immersive nature of metaverse platforms improves learning effectiveness, especially for high-risk tasks such as medical procedures and technical skills that benefit from hands-on experience. However, challenges such as technological barriers, infrastructure limitations, and initial resistance from employees were identified, requiring organizations to provide adequate support and training for smooth adoption. While the upfront costs of developing and maintaining metaverse training platforms are significant, the long-term benefits—such as scalability, reduced need for physical resources, and enhanced training outcomes—outweigh these initial investments. Organizations looking to implement metaverse-based training solutions should carefully consider the required technological infrastructure, support for employees, and privacy concerns. Future research should explore advancements in metaverse technology, including AI integration, and investigate the broader adoption of these technologies across various industries, focusing on overcoming adoption barriers and measuring their long-term impact on workforce development.